Motor skills assessments: support for a general motor factor for the Movement Assessment Battery for Children-2 and the Bruininks-Oseretsky Test of Motor Proficiency-2 - Okuda,Paola Matiko Martins (2019)
Abstract Objective To evaluate the construct validity and model-based reliability of general and specific contributions of the subscales of the Movement Assessment Battery for Children-2 (MABC-2) and Bruininks-Oseretsky Test of Motor Proficiency-2 (BOT-2) when evaluating motor skills across a range of psychiatric disorders. Methods Confirmatory factor analysis (CFA) and bifactor analysis were conducted on BOT-2 data from 187 elementary school students (grades 1 to 6) (mean age: 113 ± 20 months; boys: n = 117, 62.56%) and on MABC-2 data from 127 elementary school students (grade 1) (mean age: 76 ± 2 months; boys: n = 58, 45.67%). Results The results of the CFA fit the data for multidimensionality for the BOT-2 and presented poor fit indices for the MABC-2. For both tests, the bifactor model showed that the reliability of the subscales was poor. Conclusions The BOT-2 exhibited factorial validity with a multidimensional structure among the current samples, but the MABC-2 showed poor fit indices, insufficient to confirm its multidimensional structure. For both tests, most of the reliable variance came from a general motor factor (M-factor), therefore the scoring and reporting of subscale scores were not justified for both tests.